Temporal samples of visual information guides skilled interception - Müller, Sean; Beseler, Bradley; Morris-Binelli, Khaya; Mesagno, Christopher (Frontiers in Psychology, 2024)
This study investigated whether performance of an interceptive skill requires an intact visualperception-action cycle. Eleven skilled male Australian rules football athletes (Mage = 17.54, SD = 0.15) were recruited from an elite developmental pathway squad for a within-subject study. Participants were required to kick a ball directly at a goal from a 20-meter distance whilst wearing a pair of stroboscopic glasses. The glasses were used to create four vision conditions. Condition one kept intact the visual-perception-action cycle with uninterrupted vision of the motor skill. Three other conditions included stroboscopic vision that presented temporal samples of vision, which interrupted the perception-action cycle through progressive increases to intermittent vision occlusion of the motor skill. Goal kick error of ball position relative to a central target line within the goal and number of successful goals kicked were measured. Written report of internal and external focus of attention was also measured after each vision condition. Generalized estimating equation analysis did not reveal a significant decrement in kick target error, nor accuracy of goals scored, across normal to stroboscopic vision conditions. Performance was maintained despite a shift in attention focus from external to internal across normal to stroboscopic vision conditions. These findings have theoretical and practical implications for the visual regulation of skilled interceptive actions.